Pengembangan Sistem Informasi Manajemen Penjualan Aksesoris Motor Berbasis Web - Tarigan, Julio Putra; Dharma, Abdi; Aisyah, Siti; Sitanggang, Delima; Saragi, Yosua Morales; Turnip, Mardi (Universitas Methodist Indonesia, 2024)
In this era of globalization, computerized systems have been used by many parties, both agencies, organizations and educational institutions. A computerized system is an information system that will design transaction data into useful information and aims to help make efficient decisions. However, at this time, PT. Surya Mandiri Motor does not yet use a computerized system, so errors often occur in recording, calculating transaction data, there are difficulties in searching for data and difficulties in making reports. This sales information system can be a solution that can simplify data processing so that the sales transaction process will be faster, more precise and accurate. This system was built using the PHP programming language and MySQL database.